Face similarity linkage: A novel biometric approach to sexually motivated serial killer victims. Issue 6 (23rd July 2020) - Hackett, Sarah Bernadette; Keatley, David; Chapman, Brendan
Abstract: Some sexually motivated serial killers target victims on the basis of appearance. Therefore, multiple victims of a single serial killer are likely to have some facial features and geometries that are similar. The current research was undertaken to propose a technique, termed face similarity linkage, to evaluate whether victims of a serial killer have statistically more similar facial measurements than a randomly chosen person of the same gender. To test this, three of Ted Bundy's victims were randomly selected and anatomical landmarks were located and measured to produce proportionality indices of their faces. A random subject from an online database was used as a comparison. The results showed there were no statistically significant differences between the three of Bundy's victims, however there was significant difference between 11 of the 17 facial measurements of Bundy's victims when compared to a random person. This research serves as a proof of concept that, with more advanced means of data collection, may be a useful tool for law enforcement for linking serial homicides. The current method is relatively novel, and in need of expert systems interfaces to improve speed and application, which is outlined in the current study.